Ex-Vivo Study, The Effect of Standardized Eurycoma longifolia Extract on The Enzyme Activity of Rosiglitazone N-Demethylase - Purwantiningsih Purwantiningsih; Abas Hj Hussin; Kit Lam Chan (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Eurycoma longifolia (E. longifolia) or also known as Earth Pasak in Indonesia, has been used widely, especially to increase stamina in men. The use of herbal medicines in the long run opens up the opportunities for the influence of herbal medicines on metabolic process of other substances. This study aimed to evaluate the effect of E. longifolia extract on rosiglitazone metabolism after oral administration for one and fourteen days, and its effect on rat body weight. The rats were divided into two groups, group for one day treatment (divided into 8 subgroups with n = 6: I (control), II to VIII (were given extract at doses of 1 to 1000 mg / kg BW) and 14 days (rats divided into 4 subgroups, n = 6 : I (control), II to IV (treated with extracts of doses 5, 25 and 50 mg / kg BW). At the end of the experiment, test animals were sacrificed and rosiglitazone N-demethylase activity in hepatocytes was determined by measuring the amount of formaldehid formed at 415 nm. The rosiglitazone N-demethylase activity in all groups was analyzed by analysis of variance (ANOVA) and Tukey Test (P <0.05). The percentage of the changing in the body weight in the 14 days treatment group was compared to the control group. The results showed there was a significant increased in the rosiglitazone N-demethylase activity after rats were treated with E. longifolia extract at doses of 5 to 1000 mg / kg BB, but was not significantly different at a dose of 1 mg / kg BW when compared with control group. For the 14 days treatment, there was no significant difference between the treatment group and the control group, both for the rosiglitazone N-demethylase enzyme activity or the changed of rat body weight.